Southern Hemisphere sea-surface temperatures during the Cenomanian–Turonian: Implications for the termination of Oceanic Anoxic Event 2 - Robinson, SA; Dickson, A; Pain, A; Jenkyns, HC; O'Brien, C; Farnsworth, A; Lunt, D (Geological Society of America, 2019)
Mesozoic oceanic anoxic events (OAEs) were major perturbations of the Earth system, associated with high CO2 concentrations in the oceans and atmosphere, high temperatures, and widespread organic-carbon burial. Models for explaining OAEs and other similar phenomena in Earth history make specific predictions about the role and pattern of temperature change, which can be tested through comparison with the geological record. Oceanic Anoxic Event 2 (OAE 2) occurred ~94 m.y. ago and is commonly considered as the type example of an OAE. However, temperature change during this event is constrained largely from Northern Hemisphere sites. In order to understand whether such records represent global patterns, we use an organic geochemical paleothermometer (TEX86) to provide the first detailed Cenomanian–Turonian record of paleotemperatures from the Southern Hemisphere (Ocean Drilling Program Site 1138; paleolatitude of ~47°S). Consideration of this record, Northern Hemisphere records, and general circulation model simulations suggests that global temperatures peaked during OAE 2 but remained high into the early Turonian due to elevated CO2. These results suggest that the burial of organic carbon during the whole of OAE 2 did not, of itself, lead to global cooling and that CO2 remained high into the early Turonian. This climatic evolution suggests that cooling was not the driving mechanism for the termination of OAE 2 and that cessation of widespread anoxic conditions required changes in other factors, such as sea levels, the availability of easily weathered silicate rocks, and/or nutrient sequestration in black shales.